Challenges Faced by Students in Online Architectural Design Studio During COVID-19 Pandemic: Universities in Sarawak - Mervyn Hsin Jyi, Wong; Mohd Afzan, Mohamed; Raja Nur Syaheeza, Raja Mohd Yazit; Joanne Chui Ying, Ho (Springer, Singapore, 2023)
This paper attempts to identify the challenges faced by architecture students, learning in an online studio environment during the COVID-19 pandemic. In complying with COVID-19 Standards of Operations (SOPs), schools and universities in Sarawak, Malaysia, were closed and classes were forced to be conducted online. Despite prior integration of ICT-based learning into the architecture curriculum, the Architectural Design Studio subject still utilizes the conventional method for teaching and learning. Normally, Architectural Design Studio is conducted in a physical environment where lecturers would demonstrate critical hands-on skills such as drawing and model-making techniques, and conducting critique sessions and site analysis, all of which require students to participate in-person. Unfortunately, all of these activities were forced to be adapted to facilitate online-and-distanced learning due to the pandemic. As a result, students encountered several problems during the switch to the virtual design studio. The purpose of this study is to recognize the setbacks experienced by students in order to generate solutions that may improve the quality of online Architectural Design Studio. The research employs a quantitative descriptive study conducted using a survey method. The data was collected from undergraduate students from two architectural schools in Sarawak, namely the University of Malaysia, Sarawak (UNIMAS) and the University College of Technology Sarawak (UCTS) via a Google Forms questionnaire distributed to the students through WhatsApp groups. The analysis of students’ responses confirms that Architectural Design Studio carried out in the conventional method is more effective than when conducted online. The results indicate that the major disadvantages of the online studio were the lack of infrastructure, poor Internet connection, limitations in project materials and data collection for site analysis, imbalance in levels of digital competency, and inefficacy of doing studio work at home. This paper will identify the current online teaching method’s flaws that impede our progress toward a more resilient future in architecture.